2019
DOI: 10.1111/jrh.12350
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Sun Protection Behaviors Between Rural and Urban Communities in Texas

Abstract: Purpose:The increasing incidence of skin cancer is a global health issue. In order to identify at-risk populations in Texas, we compared sun protection behaviors and sunburn history across rural and urban counties. Methods:An online health screening survey collected data from a nonprobability sample of Texas residents in 2018. Data were weighted by sex, age, race, and ethnicity. Multinomial multivariable logistic regression identified key factors associated with sun protection behaviors and sunscreen use. Weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 26 publications
2
21
1
2
Order By: Relevance
“…A recent manuscript from 2018 that reviewed articles targeting behavioral interventions in skin cancer determined that there was little progress in multi-intervention skin cancer behavioral interventions across the United States from 2000 to 2015 with research gaps including detecting skin cancer in high-risk populations, dissemination studies, and behavioral interventions ( Geller et al, 2018 ). While prior research supports an influence of rural/urban areas in the practice of sun protective behaviors, our research does not support a difference by geographic location ( Cunningham et al, 2019 , Zahnd et al, 2010 ). Future public health campaigns often led by the CDC, other anti-cancer organizations, and family foundations should choose to focus on demographic disparities more so than geographic influence while deepening our understanding of how acculturation affects sun protective behaviors ( Andreeva et al, 2009 ).…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…A recent manuscript from 2018 that reviewed articles targeting behavioral interventions in skin cancer determined that there was little progress in multi-intervention skin cancer behavioral interventions across the United States from 2000 to 2015 with research gaps including detecting skin cancer in high-risk populations, dissemination studies, and behavioral interventions ( Geller et al, 2018 ). While prior research supports an influence of rural/urban areas in the practice of sun protective behaviors, our research does not support a difference by geographic location ( Cunningham et al, 2019 , Zahnd et al, 2010 ). Future public health campaigns often led by the CDC, other anti-cancer organizations, and family foundations should choose to focus on demographic disparities more so than geographic influence while deepening our understanding of how acculturation affects sun protective behaviors ( Andreeva et al, 2009 ).…”
Section: Discussioncontrasting
confidence: 97%
“…Keratinocyte carcinomas are also prevalent with 5.4 million cases of basal and squamous cell carcinomas diagnosed in 2012 ( American Cancer Society, 2019 ). Previous research supports that individuals living in rural areas compared to urban areas are more likely to experience a higher melanoma incidence and mortality ( Cunningham et al, 2019 ). Furthermore, prior research has indicated that regional differences in sun protective measures exist, with rural individuals from the Midwest and South being less likely to use sunscreen ( Zahnd et al, 2010 ).…”
Section: Introductionmentioning
confidence: 87%
“…Obwohl aktuelle Studien für Deutschland einerseits auf ein geringeres Hautkrebsrisiko andererseits auf eine spätere Diagnosestellung sowie Behandlung von Hautkrebs für die ländliche Bevölkerung verglichen mit der Stadtbevölkerung hinweisen [3,17], liegen bisher kaum Daten zur Inanspruchnahme von Sonnenschutzmaßnahmen in der ländlichen Bevölkerung Deutschlands vor. Basierend auf Untersuchungsergebnissen anderer Länder [7,13] und verschiedener Außenberufsgruppen in Deutschland, die überwiegend im ländlichen Raum tätig sind [25,28,30], lässt sich jedoch eine geringe Anwendung von Sonnenschutzmaßnahmen in der deutschen Landbevölkerung ableiten.…”
Section: Hintergrund Und Fragestellungunclassified
“…Wie auch in anderen Studien war Sonnencreme in der vorliegenden Untersuchung die am häufigsten berichtete Sonnenschutzmaßnahme [2,20]. Vergleicht man die Werte der ländlichen Bevölkerung in dieser Untersuchung allerdings mit Daten zur Stadtbevölkerung Deutschlands [2], lässt sich ähnlich wie in anderen Ländern [7,13] In der vorliegenden Arbeit wird bei derEinteilung inRisikogruppendeutlich, dass das männliche Geschlecht mit inadäquatem Präventionsverhalten assoziiert war, was im Konsens mit früherer Literatur ist [11,13,14,18,24] und vermutlich mitunter auf ein geringeres Gesundheitsbewusstsein der Männer zurückzuführen ist [4]. Frauen nutzten lediglich seltener eine Kopfbedeckung zum Schutz vor UV-Strahlung, was auch schon für andere Länder gezeigt werden konnte [13,14].…”
Section: Diskussionunclassified
“…For example, adolescents in Hawaii reported using sunscreen less frequently than those in California or Colorado [ 44 ]. Sun protective behaviors and sunburns also varied between urban and rural areas in Texas adults, with rural residents more likely to report using sunscreen with a higher sun protection factor (SPF), yet also report having had more sunburns during adolescence compared to urban residents [ 45 ]. We documented significant clustering of model residuals that may suggest some of the coefficient variance and significance tests may be biased.…”
Section: Discussionmentioning
confidence: 99%